If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-13x^11=x(x)
We move all terms to the left:
-13x^11-(x(x))=0
We do not support expression: x^11
| 19+6m=25 | | n–7+70=66 | | 2x-1=x+(-6) | | -13x11=6(x) | | -20-10e=-70 | | 30t+25=-20t+100 | | 15+2.50r=30 | | 10x2+8x=1 | | x-16=42/6 | | Y=2x+350 | | 5x+3=17-9x | | 12+a/2=14 | | 7x+4=-6x-9 | | -13+2m=3 | | 21c=14+7c | | 4x+18+44=180 | | 26-5a=1 | | 3x=2x+110 | | x^2-7x-34=8-6x | | 3(–u+11)–18=15 | | 8x–34=2x-10 | | 10g=26-3g | | 4x+18=44 | | 54x=23 | | 16-x=42(6) | | 10x+10+12x-10=180 | | 83=x-17 | | 3x+6x-55=49 | | -3u-5=-17 | | x-16=42÷6 | | 13+7x=27 | | 0.3x0.9=0.27 |